IDIOMATICS OF THE AVANT-GARDE: ELABORATING THE IDIOM ID CARD IN THE AVANT-GARDE DISCOURSE (Philological Studies, 2019)
The paper sets out to explore the problem of the idiom identification in the avant-garde discourse. In particular, the research is aimed at studying the frame of “idiom” in the cubo-futurists' manifestoes of the 1910th – the beginning of the 1920s that are devoted to the issues of linguistic creativity in the literary or artistic activity. As a result, the main categorial characteristics of the avant-garde idioms proper have been established; such key notions of the present study as “idiomatics of the avant- garde” and “the avant-garde idiom ID card” have been elaborated.
Keywords: method of idiom identification, idiomatics, avant-garde discourse, language experiment, cubo-futurism, manifesto, ID of the avant-garde idiom